Site- and structure-specific characterization of glycoproteins of H11: potent vaccine candidates against parasitic worm Haemonchus - Liu, Xin; Liu, Feng; Liu, Hui; Ye, Lisha; Zhang, Yao; Peng, Wenjie; Gupta, Nishith; Hu, Min; Wang, Chunqun (Frontiers in Immunology, 2026)
Parasitic worm (helminth) infections pose significant threats to global health and livestock productivity. Although mass spectrometry (MS)-based glycomics have revealed that helminths express structurally complex N-glycans, site- and structure-specific characterization of intact glycopeptides remains a major challenge. Here we employed advanced MS-based intact glycoproteomics to explore the N-glycosylation profile of H11 antigen – an important vaccine antigen derived from the pathogenic parasite Haemonchus contortus. We identified seven glycosylated aminopeptidases carrying 19 N-glycosylation sites with 31 distinct N-glycan structures. Notably, 13 N-glycopeptides were significantly enriched by H11-induced protective IgG antibodies. Our results revealed extensive structural heterogeneity and abundant core fucosylation among the identified N-glycopeptides. Additionally, molecular docking analyses demonstrated that these IgG-recognized N-glycopeptides were located on the protein surface or near substrate-access channels, indicating their potential as antigenic epitopes. Overall, this work provides a precise glycoproteomic characterization of a key helminth antigen and offers valuable insights for the rational design of vaccines against H. contortus and other related parasitic species.